Macrophage Foam Cell–Derived Extracellular Vesicles Promote Vascular Smooth Muscle Cell Migration and Adhesion. Issue 10 (October 2016) - Niu, Chenguang; Wang, Xu; Zhao, Mingming; Cai, Tanxi; Liu, Peibin; Li, Jizhao; Willard, Belinda; Zu, Lingyun; Zhou, Enchen; Li, Yufeng; Pan, Bing; Yang, Fuquan; et al.
Abstract : Background: A new mechanism for intercellular communication has recently emerged that involves intercellular transfer of extracellular vesicles (EVs). Several studies have indicated that EVs may play a potential role in cell‐to‐cell communication between macrophage foam cells and vascular smooth muscle cells (VSMCs) in atherosclerotic lesion. Methods and Results: This study involved the comparison of circulating EVs from atherosclerotic patients and control participants. The results showed that the circulation of the patients contained more leukocyte‐derived EVs and that these EVs promoted more VSMC adhesion and migration than those of healthy participants. We then established a macrophage foam cell model and characterized the EVs from the macrophages. We used flow cytometric analyses and cell migration and adhesion assays and determined that the foam cells generated more EVs than the normal macrophages and that the foam cell–derived EVs were capable of promoting increased levels of VSMC migration and adhesion. Furthermore, we performed a proteomic analysis of the EVs. The data showed that the foam cell–derived EVs may promote VSMC adhesion and migration by regulating the actin cytoskeleton and focal adhesion pathways. In addition, Western blotting revealed that foam cell–derived EVs could promote the phosphorylation of ERK and Akt in VSMCs in a time‐dependent manner. We also found that foam cell–derived EVs could enter the VSMCs and transfer integrins to the surface of these cells. Conclusions: The data in our present study provide the first evidence that EVs from foam cells could promote VSMC migration and adhesion, which may be mediated by the integration of EVs into VSMCs and the subsequent downstream activation of ERK and Akt.